Canopy indices to quantify the economic optimum nitrogen rate in processing potato - Giletto, Claudia Marcela; Echeverria, Hernan Eduardo (Springer, 2019)
In-season N applications to processing potato crops may increase profits and improve N fertilizer use efficiency. The objective of our study was to evaluate indices to predict the differential economic optimum N rate (dEONR) using a SPAD 502 chlorophyll meter, a Crop Circle ACS-210 (CC), and a Green Seeker 506 (GS). Additionally, algorithms were developed to determine N fertilizer variable rates. The relative chlorophyll meter reading (RCM), the relative chlorophyll index (RCI), and the relative normalized differential vegetative index (RNDVI) were calculated using the mean sensor value divided by the value determined in plots with the highest N rate within each site-year. The relationship between relative indices and dEONR was evaluated by fitting quadratic and quadratic-plateau regression models. The canopy chlorophyll indices (RCM and RCI) were significantly associated with dEONR during the growing season (R2 = 0.48, 0.22 at 40 days after planting (DAP), R2 = 0.28, 0.73 at 60 DAP, R2 = 0.62, 0.82 at 80 DAP, R2 = 0.58, 0.83 at 100 DAP for RCM and RCI, respectively). The canopy biomass index (RNDVI) was significantly associated with dEONR only at tuber bulking (R2 = 0.51, 0.85 at 80 DAP and R2 = 0.48, 0.51 at 100 DAP, for GS and CC, respectively). The canopy chlorophyll indices performed better than the canopy biomass indices in measuring N stress. The optical sensor CC was better than the GS in predicting N stress because it measures the RNDVI and the RCI in a single reading.